Mainstreaming Functional Positions within Indonesian Bureaucracy: Half-Hearted Commitment to Professionalization? - Antonius Galih Prasetyo (Puslatbang KDOD Lembaga Administrasi Negara, 2022)
The Indonesian government has declared bureaucratic simplification as one of its strategic targets. Based on the understanding that a functional (professional) position is the key to increasing the professionalism of civil servants, a massive